Design and Evaluation of a User-Centric Cryptographic Model Leveraging Hybrid Algorithms for Secure Cloud Storage and Data Integrity (American Journal of Innovation in Science and Engineering, 2025)
The exponential growth of cloud computing has created an urgent need for advanced cryptographic solutions that ensure data security while maintaining usability and performance. This study presents a novel hybrid cryptographic model that integrates Advanced Encryption Standard (AES), Data Encryption Standard (DES), and RC6 algorithms to address the limitations of conventional systems. By combining the robust security of AES and RC6 with the compatibility of DES, the proposed model achieves enhanced encryption speed, scalability, and resistance to sophisticated attacks. The model incorporates user-centric features, such as automated key management and passwordless authentication, to simplify encryption workflows and reduce user errors, making it accessible to a broad spectrum of users. Comprehensive testing and user feedback analysis reveal that the hybrid model significantly outperforms traditional cryptographic systems in key areas, including encryption and decryption speeds, user error rates, and system responsiveness. The proposed framework demonstrates a 25% improvement in performance metrics and a 40% increase in resistance to brute-force and differential attacks. User satisfaction rates exceed 90%, reflecting the success of usability enhancements. Despite its strengths, the study acknowledges certain limitations, such as computational intensity and the need for quantum-resistant mechanisms, which will be addressed in future research. The findings underscore the potential of this hybrid model as a secure, scalable, and user-friendly solution for modern cloud storage environments, paving the way for widespread adoption and further innovation in cryptographic systems.